Answer :

We have

x + 2y = -1 …(i)

2x – 3y = 12 …(ii)

From equation (i),

x + 2y = -1

⇒ x = -2y – 1 …(iii)

Substituting the value of x from equation (iii) in equation (ii), we get

2(-2y – 1) – 3y = 12

⇒ -4y – 2 – 3y = 12

⇒ -7y – 2 = 12

⇒ -7y = 2 + 12

⇒ -7y = 14

⇒ y = -2

Putting this value of y in equation (iii), we get

x = -2(-2) – 1

⇒ x = 4 – 1

⇒ x = 3

**Thus, we get the solution as x = 3 and y = -2.**

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Pair of Angles29 mins

Angle Sum Property29 mins

Parallel Lines and Transversal Lines22 mins

Equations of Motion41 mins

Subject Verb Agreement36 mins

Mixed Bag40 mins

Eliminating India's Poverty48 mins

Dangling Modifier43 mins

Poverty in India51 mins

People As Resources53 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation